Pengaruh Current Ratio, Inventory Turn Over, Dan Total Asset Turn Over Terhadap Profitabilitas (ROA) Pada PT. Perkebunan Nusantara III (Persero) Medan Periode 2018-2021 - Herlina Novita; Natalia Manalu; Silvia Winarti Simanjuntak; Petrus Paskah Yus Nduru; Raynaldi Dicky Sitorus (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2023)
This study aims to determine and test the Effect of Current Ratio, Inventory Turn Over, and Total Assets Turn Over on Profitability (ROA) at PT. Perkebunan Nusantara III (Persero) Medan for the 2018-2021 period. The population in this study is a report on the finances of PT. Perkebunan Nusantara III (Persero) for the 2018-2021 period. The sampling technique in this study is nonprobability sampling, namely by using saturated samples, so that the population and samples used are monthly data in 2018-2021 which amounted to 48 samples from January 2018 to December 2021. This study used classical assumption test methods and multiple linear regression analysis. Based on the results of research testing, it shows that simultaneously the Current Ratio, Inventory Turn Over, and Total Assets Turn Over have a positive and significant effect on the Profitability (Return On Assets) of PT. Perkebunan Nusantara III (Persero) Medan for the 2018-2021 period. Partially Current Ratio has a negative and significant effect on Profitability (ROA), Inventory Turn Over has a negative and significant effect on Profitability (ROA), and Total Assests Turn Over has a positive and significant effect on Profitability (ROA).